Long non‐coding RNA MEG3 silencing and microRNA‐214 restoration elevate osteoprotegerin expression to ameliorate osteoporosis by limiting TXNIP. Issue 4 (3rd January 2021) - Yang, ChangSheng; Gu, ZhengTao; Ding, Rui; Huang, CaiQiang; Li, QingChu; Xie, DengHui; Zhang, RongKai; Qiu, YiYan
Abstract: Studies have shown that long non‐coding RNA (lncRNA) MEG3 plays a key role in osteoporosis (OP), but its regulatory mechanism is somewhat incompletely clear. Here, we intend to probe into the mechanism of MEG3 on OP development by modulating microRNA‐214 (miR‐214) and thioredoxin‐interacting protein (TXNIP). Rat models of OP were established. MEG3, miR‐214 and TXNIP mRNA expression in rat femoral tissues were detected, along with TXNIP, OPG and RANKL protein expression. BMD, BV/TV, Tb.N and Tb.Th in tissue samples were measured. Ca, P and ALP contents in rat serum were also determined. Primary osteoblasts were isolated and cultured. Viability, COL‐I, COL‐II and COL‐Χ mRNA expression, PCNA, cyclin D1, OCN, RUNX2 and osteolix protein expresion, ALP content and activity, and mineralized nodule area of rat osteoblasts were further detected. Dual‐luciferase reporter gene and RNA‐pull down assays verified the targeting relationship between MEG3, miR‐214 and TXNIP. MEG3 and TXNIP were up‐regulated while miR‐214 was down‐regulated in femoral tissues of OP rats. MEG3 silencing and miR‐214 overexpression increased BMD, BV/TV, Tb.N, Tb.Th, trabecular bone area, collagen area and OPG expression, and down‐regulated RANKL of femoral tissues in OP rats. MEG3 silencing and miR‐214 overexpression elevated Ca and P and reduced ALP in OP rat serum, elevated osteoblast viability, differentiation ability, COL‐I and COL‐Χ expression and ALP activity, and reduced COL‐II expression of osteoblasts. MEG3 specifically bound to miR‐214 to regulate TXNIP. MEG3 silencing and miR‐214 overexpression promote proliferation and differentiation of osteoblasts in OP by down‐regulating TXNIP, which further improves OP.